Diagnosis and therapy before assisted reproductive treatments. Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF register number 015-085, February 2019) - Part 1, Basic assessment of the woman = Diagnostik und Therapie vor einer assistierten reproduktions-medizinischen Behandlung. Leitlinie der DGGG, OEGGG und SGGG (S2k Level, AWMF-Registernummer 015-085, Februar 2019) - Teil 1, grundlegende Abklärung der Frau - Toth, Bettina; Kuon, Ruben-Jeremias; Strowitzki, Thomas; Wischmann, Tewes (Geburtshilfe und Frauenheilkunde, 2019)
Introduction: Supporting and counselling couples with fertility issues prior to starting ART is a multidisciplinary diagnostic and therapeutic challenge. The first German/Austrian/Swiss interdisciplinary S2k guideline on “Diagnosis and Therapy Before Assisted Reproductive Treatments (ART)” was published in February 2019. This guideline was developed in the context of the guidelines program of the German Society of Gynecology and Obstetrics (DGGG) in cooperation with the Swiss Society of Gynecology and Obstetrics (SGGG) and the Austrian Society of Gynecology and Obstetrics (OEGGG). Aims: One third of the causes of involuntary childlessness are still unclear, even if the woman or man have numerous possible risk factors. Because the topic is still very much taboo, couples may be socially isolated and often only present quite late to a fertility center. At present, there is no standard treatment concept, as currently no standard multidisciplinary procedures exist for the diagnostic workup and treatment of infertility. The aim of this guideline is to provide physicians with evidence-based recommendations for counselling, diagnostic workup and treatment. Methods: This S2k guideline was developed on behalf of the Guidelines Commission of the DGGG by representative members from different professional medical organizations and societies using a structured consensus process. Recommendations: The first part of this guideline focuses on the basic assessment of affected women, including standard anatomical and endocrinological diagnostic procedures and examinations into any potential infections. Other areas addressed in this guideline are the immunological workup with an evaluation of the patientʼs vaccination status, an evaluation of psychological factors, and the collection of data relating to other relevant factors affecting infertility. The second part will focus on explanations of diagnostic procedures compiled in collaboration with specialists from other medical specialties such as andrologists, human geneticists and oncologists.
Gesehen am 27.01.2020